China approach in a changing world - Chen, Ping (2009)
The Washington Consensus failed to recognize the need of the developing world and the limits of the western mode of industrialization. In last three decades, China experiments a new approach with self-determination, open-minded learning, decentralized experiments, and dual-track reform to simultaneously achieve high speed growth, social stability, and international partnership in peaceful development.